Genetic Labeling of Cells Allows Identification and Tracking of Transgenic Platelets in Mice - Krüger, Irena (Int J Mol Sci, 2021)
Background: The use of knock-out mouse models is crucial to understand platelet activation and aggregation. Methods: Analysis of the global double fluorescent Cre reporter mouse mT/mG that has been crossbred with the megakaryocyte/platelet specific PF4-Cre mouse. Results: Platelets show bright mT (PF4-Cre negative) and mG (PF4-Cre positive) fluorescence. However, a small proportion of leukocytes was positive for mG fluorescence in PF4-Cre positive mice. In mT/mG;PF4-Cre mice, platelets, and megakaryocytes can be tracked by their specific fluorescence in blood smear, hematopoietic organs and upon thrombus formation. No differences in platelet activation and thrombus formation was observed between mT/mG;PF4-Cre positive and negative mice. Furthermore, hemostasis and in vivo thrombus formation was comparable between genotypes as analyzed by intravital microscopy. Transplantation studies revealed that bone marrow of mT/mG;PF4-Cre mice can be transferred to C57BL/6 mice. Conclusions: The mT/mG Cre reporter mouse is an appropriate model for real-time visualization of platelets, the analysis of cell morphology and the identification of non-recombined platelets. Thus, mT/mG;PF4-Cre mice are important for the analysis of platelet-specific knockout mice. However, a small proportion of leukocytes exhibit mG fluorescence. Therefore, the analysis of platelets beyond hemostasis and thrombosis should be critically evaluated when recombination of immune cells is increased.